A cross-sectional study to assess pattern in wrinkle formation in different age groups in female population in Kelantan - Jimeno IV, Zosimo Ken L. (2018)
Background Facial wrinkles encompasses superficial and mimetic wrinkles, and facial lines; formation of which are combined effect of intrinsic and extrinsic factors. Quantitative study of facial wrinkles using photographic methods enables researchers to measure the amount of wrinkles on specific area, and in this case the face. The aim of this study is to determine the means of facial wrinkles in female population of different age groups in Kelantan. Methods A total of 168 women aged 20 to 48 years old, were recruited in this study based on convenience sampling. Subjects were divided equally into 3 age groups (later adolescence, early adulthood and middle adulthood). Digital photography of subject’s frontal view of face at zero degree was taken using device developed by OptoBioMed (Korea). Measurement of wrinkles at glabella, forehead and frontal face were calculated using provided software. Results Wrinkle formation was more marked at all assessed regions in the older age group (p<0.01). Glabella showed an area more affected than forehead. In each age cohort, the formation of wrinkles in glabella and forehead showed positive correlation (p<0.05, Pearson Correlation Test). Conclusion The results of this present study showed progressive increase of facial wrinkles, more significantly in the older age group. The formation of facial wrinkles was expected to progress simultaneously as shown by their positive correlation.